Study of incubation and Hatching Rate of Common moorhen, Gallinula chloropus in the South Kashmir wetlands - Farooq Ahmad Bhat Dr. Preeti Upadhyay Prof. (Dr) Mohammad Farooq Mir (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
The study was carried out in three wetlands of South Kashmir viz Fashkoori, Manibugh and Chandhara-Kranchu during the breeding seasons of 2018 & 2019 focusing on the incubation & survival rates of eggs of Common moorhen, Gallinula chloropus. The nests were searched and marked by long stakes flagged with green strips. The female arranged the eggs to ensure they were fully covered during the incubation and dedicated maximum time of the day for incubation, while the male remained nearby to protect the nests and eggs. The male incubated the eggs during night and when the female left the nests for feeding. The female continuously rearranged the eggs for uniform incubation, completing the process within 17 to 22 days. Hatching success rate was influenced by presence of dense, tall vegetation and number of predators, with Fashkoori wetland has highest predation loss at 16.85%, while Chandhara-Kranchu has the greatest loss due to the faulty incubation at 20.63%. Overall, 15.87% eggs were lost by predators and 19.23% eggs by faulty incubation. Hatching was asynchronous with slight variation in hatching success rates during two years of study i.e. 65.09% in 2018 and 64.71% in 2019, resulting in an average success rate was 64.90%.